Machine Learning Risk Prediction Model of 90-day Mortality After Gastrectomy for Cancer. Issue 5 (22nd November 2022) - Pera, Manuel; Gibert, Joan; Gimeno, Marta; Garsot, Elisenda; Eizaguirre, Emma; Miró, Mónica; Castro, Sandra; Miranda, Coro; Reka, Lorena; Leturio, Saioa; González-Duaigües, Marta; Codony, Clara; et al.
Abstract : Objective: To develop and validate a risk prediction model of 90-day mortality (90DM) using machine learning in a large multicenter cohort of patients undergoing gastric cancer resection with curative intent. Background: The 90DM rate after gastrectomy for cancer is a quality of care indicator in surgical oncology. There is a lack of well-validated instruments for personalized prognosis of gastric cancer. Methods: Consecutive patients with gastric adenocarcinoma who underwent potentially curative gastrectomy between 2014 and 2021 registered in the Spanish EURECCA Esophagogastric Cancer Registry database were included. The 90DM for all causes was the study outcome. Preoperative clinical characteristics were tested in four 90DM predictive models: Cross Validated Elastic regularized logistic regression method (cv-Enet), boosting linear regression (glmboost), random forest, and an ensemble model. Performance was evaluated using the area under the curve by 10-fold cross-validation. Results: A total of 3182 and 260 patients from 39 institutions in 6 regions were included in the development and validation cohorts, respectively. The 90DM rate was 5.6% and 6.2%, respectively. The random forest model showed the best discrimination capacity with a validated area under the curve of 0.844 [95% confidence interval (CI): 0.841–0.848] as compared with cv-Enet (0.796, 95% CI: 0.784–0.808), glmboost (0.797, 95% CI: 0.785–0.809), and ensemble model (0.847, 95% CI: 0.836–0.858) in the development cohort. Similar discriminative capacity was observed in the validation cohort. Conclusions: A robust clinical model for predicting the risk of 90DM after surgery of gastric cancer was developed. Its use may aid patients and surgeons in making informed decisions.